Stosunek do przeciwników politycznych w kampaniach wyborczych – próba oceny etycznej - Walerjan, Bożena (Annales. Etyka w Życiu Gospodarczym, 2008)
The election campaigns in Poland have become oriented to the still more extent on fighting backthe political opponents. Only seldom we can watch skirmishes about programmes and battles withthe use of substantial arguments. Instead, we observe more and more mutual accusations, personalreproaches and attempts of slandering the opponent using unethical methods. The attitude of onepolitician to another assumed quite special features both on the level of verbal behaviour and theirattitudes. Almost in every election campaign since the year 1989 the voters have had the occasionsto observe the behaviours of politicians which were far from the moral standards and whichsignificantly lowered the level of political culture in Poland. Since a few years rival discreditations,intrigues, announcing untrue information about opponents and creation of media facts have dominatedduring the election battles. Occurrences of such type are crucial for political alienation amongthe citizens and contribute to preservation of a negative picture of the politics itself as a sort ofdishonest and immoral activity. Various methods of depreciation of opponents are still more and morewillingly used. This paper will discuss selected behaviours of political competitors towards each other;also an attempt will be undertaken to assess those behaviours from the ethics’ point of view.